Preface: 2nd International Conference on Artificial Intelligence, Database and Machine Learning (AIDML 2024) - Arthur, Humphrey; Huang, Fan (Transactions on Computer Science and Intelligent Systems Research, 2024)
The 2024 2nd International Conference on Artificial Intelligence, Database and Machine Learning (AIDML 2024) was held in Rotterdam, Netherlands during July 06-07, 2024. This annual event aims to serve as an international forum to gather academicians, scientists, engineers, and researchers working in the fields of algorithms, big data, computing, artificial intelligence, and machine learning to exchange views, share their professional knowledge, experience, and research results, and discuss the challenges and future directions in their professional fields. AIDML 2024 will mainly feature keynote speeches and peer-reviewed paper speeches. In addition, social activities or academic visits will be arranged to encourage exchanges, discussions, or cooperation between researchers. The conference also had many invited lectures and workshops which discuss many in-depth topics related to the main themes. We sincerely hope that AIDML 2024 would not only show the participants a broad overview of the latest research results, but also provide them with a significant platform for academic connection and exchange. We would like to express our sincere gratitude to all the keynote speakers, reviewers, and editors for their hard work, precious time and endeavor preparing for the conference. AIDML 2024 Organizing Committee Rotterdam, Netherlands